FOOD COLORS OF VEGETABLE RAW MATERIALS, THEIR PHYSICAL AND CHEMICAL PROPERTIES - H. Usmonjonova (International Journal of Innovations in Engineering Research and Technology, 2021)
The use of fruits and vegetables is important due to their rich chemical composition and high nutritional value. Nature colored fruits and vegetables in a wide range. Leaves, stems, roots and ripened fruits of plants are a source of colors. These sources are widely used in the color formation of food products and beverages. In industry, food colors are extracted from plant materials and their secondary products. As an example, we analyze several varieties of plants belonging to the Amarantus family. Amaranth seeds are used in traditional medicine, national cuisine in cooking, and in industry. A mixture of amaranth grains with corn is used in the preparation of cereals, it is widely used in the manufacture of confectionery. Amaranth has been used in medicine since ancient times for the treatment of wounds, skin diseases (measles, rubella), weight loss, obesity, cardiovascular diseases, with impaired liver and kidney function, and the elimination of bad breath. Amaranth is a one-year plant, grown in various directions of use, for example, as vegetables (Amaranthus gangeticus, Amaranthus mangostanus), cereal (Amaranthus caudatus, Amaranthus paniculatus), ornamental (Amaranthus blitum), and food purpose [1,3–9]. The most valuable m healing part of amaranth is its seeds. 100 g of amaranth seeds contain energy of 370 calories, 7 g of lipids, 4 mg of sodium, 508 mg of potassium, 65 mg of carbohydrates, 1.7 mg of sugars, 14 mg of protein, 159 mg of calcium, 4.2 mg of vitamin C, 7.6 mg of iron, 248 mg of magnesium, 0.6 mg of vitamin B6, B2-riboflavin, B1-thiamine, rare forms of vitamin E tocopherol and tocotriene, vitamin D, pantogenic acid, squalene. Naturally, amaranth oil does not contain cholesterol, it is secreted by the content of serotonin, which is important for the human organizm, and red pigments, for example xanthine, as well as bile acid, choline, and steroids.